2013
DOI: 10.3390/app3030624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rapid Stain IDentification (RSID™) Reader System for Analysis and Documentation of RSID™ Tests

Abstract: Abstract:The ability to detect the presence of body fluids is a crucial first step in documenting and processing forensic evidence. The Rapid Stain IDentification (RSID™) tests for blood, saliva, semen and urine are lateral flow immunochromatographic strip tests specifically designed for forensic use. Like most lateral flow strips, the membrane components of the test are enclosed in a molded plastic cassette with a sample well and an observation window. No specialized equipment is required to use these tests o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It is a device designed to perform an optical interrogation of the test cassette and is useful in resolving ambiguous (very faint band) results, but is not required for correct or proper interpretation of strip test results. 31 In our study we did not experience any ambiguous results. Another limitation is that we only tested triatomines with a visible blood meal.…”
Section: Discussionmentioning
confidence: 54%
“…It is a device designed to perform an optical interrogation of the test cassette and is useful in resolving ambiguous (very faint band) results, but is not required for correct or proper interpretation of strip test results. 31 In our study we did not experience any ambiguous results. Another limitation is that we only tested triatomines with a visible blood meal.…”
Section: Discussionmentioning
confidence: 54%
“…Saliva can be probably identified and typed by many amylase assays. These forensic methods for human saliva detection have many drawbacks as lack of specificity, lack of sensitivity, difficult protocols or it can consume big amount of the biological sample (Sinelnikov et al,. 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These techniques provide a target area for swabbing for subsequent confirmation and DNA tests. Sinelnikov et al, (2013) reported that numerous experiments using RSID TM -Saliva kit demonstrating the ability of the test to detect dried human saliva stains from a variety of objects that are typically encountered in forensic laboratory case work; as cups, glass, metal, fabrics, plastic, etc. The previous study recommended also the usage of a handheld reader capable of recording and scoring the tests to resolve the ambiguous (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Technical Report a) Criteria 29: It is preferable to include electropherograms of all analyzed samples, including controls. b) Criteria 30: It is preferable to include any available reader reports or images for the interpretation of the generic diagnostic results [4]. c) Criteria 31: It is necessary to provide the quantification results and it is preferable to include the associated instrument reports.…”
Section: I)mentioning
confidence: 99%